A simple method for rapid determination of residual water content in rubber cup lumps - Nair, D.B.; Jacob, James; Nair, N.R. (Journal of Plantation Crops, 2012)
Estimation of yield of rubber trees based on the dry rubber content of cup lumps is a common practice in field experiments. This leads to large errors due to the presence of moisture trapped inside the lump even after prolonged drying. The amount of water trapped inside the cup lumps can vary with the size of the lump. An experiment was conducted using cup lumps of varying sizes coagulated from fresh field latex for determination of the actual water content in them. Fresh weight of the cup lump was recorded gravimetrically immediately after coagulation. An equal amount of latex was taken in aluminium pan for acid coagulation to make rubber sheet. The dry weight of cup lumps and sheets were recorded after drying and smoking. Dry sheets always recorded less dry weight than dry cup lumps as the latter always contained some amount of moisture trapped inside. Residual moisture content of the lump was calculated from the differences in the weights of dried rubber sheets and lumps. The moisture content of the dry cup lump was not constant across their sizes; the larger the cup lump, the more the residual moisture content in lump. In dry cup lumps, the water content varied from 3-13% by dry weight. In fresh cup lumps this varied from 47-53% on fresh weight basis. Regression equations were derived between per cent residual moisture content and weight of dry cup lumps. The regression equation is suitable for determination of actual rubber content in large number of lumps. Differences in estimation of rubber content using the conventional method and the equations derived from this study and possible errors in determining the rubber yield using the conventional method are discussed.